Revolution of South African public procurement in the Industry 4.0 era - Lawrence M. Mojaki; Tite Tuyikeze; Nkanyiso K. Ndlovu (Journal of Transport and Supply Chain Management)
Background: Public procurement in South Africa is challenged by conventional methods that pave the way for human interference resulting in fraud and corruption, delays, unaccountability and poor performance of the value chain in the procurement process.